Digit ratio (2D:4D): relationship with freestyle swimming performance of adolescent well-trained swimmers - Özen, G.; Atar, Ö.; Koc, H. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2019)
Purpose: The purpose of this study was to determine whether there was a relationship between the digit ratios and freestyle swimming performance of adolescent well-trained swimmers. Material and Methods: Twenty-two well-trained male swimmers who had at least 3 years of swim training experience were recruited as participants. The participants` mean age was 14.1±1.5 years, body height was 164.5±11.3 cm, and body mass was 54.4±11.2 kg. Participants` body height, mass, index finger (2D) and ring finger (4D) lengths were measured and digit ratio (2D:4D) and body mass index of participants was calculated. To determine the swimming performance of participants, the short (50m and 100m) and middle (200m and 400m) distance freestyle time-trial swimming tests were performed on participants. The association between the 2D:4D ratio and the swimming performance were determined by the Pearson correlation coefficient. Results. Our findings indicated that there were strong negative correlations (r > .50) between the mean of BMI and swimming times of adolescent swimmers. ( p > .05 ). However, result of this study revealed no relationship between the digit ratio (2D:4D) and swimming performance in adolescent swimmers. ( p > .05 ). Conclusion. As a result, it may be stated that the 2D:4D ratio of swimmers is not a major parameter in predicting swimming performance for adolescent swimmers.